Synergistic effects of two types of ionic liquids on the dispersion of multiwalled carbon nanotubes in ethylene–vinyl acetate elastomer: preparation and characterization of flexible conductive composites. Issue 12 (1st March 2017) - Cao, Xiaojun; Jin, Mingyue; Liang, Yuanyuan; Li, Yongjin
Abstract: Flexible conductive composites based on an elastomer, ethylene–vinyl acetate copolymer (EVM), and multiwalled carbon nanotubes (MWCNTs) were fabricated by melt‐blending and subsequent crosslinking. Two types of ionic liquids (ILs), tributylmethylammonium bis(trifluoromethanesulfonyl)imide and 1‐ethyl‐3‐methylimidazolium tetrafluoroborate, were used to modify the MWCNTs for the purpose of improving their dispersion in the polymer matrix. It was found that the MWCNTs modified by an individual IL form agglomerates in the EVM matrix, while the MWCNTs modified by the two types of ILs simultaneously disperse in the EVM matrix homogeneously. Moreover, nanocomposites based on the MWCNTs modified with the combination of the two ILs exhibit improved mechanical and electrical properties. The mechanism of such synergistic effects was investigated. It was found that EVM is miscible with tributylmethylammonium bis(trifluoromethanesulfonyl)imide and it is immiscible with 1‐ethyl‐3‐methylimidazolium tetrafluoroborate. On the other hand, MWCNTs show stronger interaction with 1‐ethyl‐3‐methylimidazolium tetrafluoroborate than tributylmethylammonium bis(trifluoromethanesulfonyl)imide. Therefore, the uniform dispersion of MWCNTs in the EVM matrix is attributed to 'bridging' effects of the two ILs due to the different interactions of the two ILs with MWCNTs and EVM. The application of MWCNTs modified with two types of ILs in a polymer matrix opens a new fabrication strategy for high‐performance polymer nanocomposites. © 2017 Society of Chemical Industry Abstract : Two types of ionic liquids simultaneously coat carbon nanotubes and bridge the carbon nanotubes with an ethylene–vinyl acetate copolymer rubber matrix. In this way, flexible conductive nanocomposites were achieved.